IFNα-induced BST2+ tumor-associated macrophages facilitate immunosuppression and tumor growth in pancreatic cancer by ERK-CXCL7 signaling - Zheng, Chenlei; Wang, Junli; Zhou, Yu; Duan, Yi; Zheng, Rujia; Xie, Yuting; Wei, Xiaobao; Wu, Jiangchao; Shen, Hang; Ye, Mao; Kong, Bo; Liu, Yunhua; et al. (Cell reports, 2024)
Pancreatic ductal adenocarcinoma (PDAC) features an immunosuppressive tumor microenvironment (TME) that resists immunotherapy. Tumor-associated macrophages, abundant in the TME, modulate T cell responses. Bone marrow stromal antigen 2-positive (BST2+) macrophages increase in KrasG12D/+; Trp53R172H/+; Pdx1-Cre mouse models during PDAC progression. However, their role in PDAC remains elusive. Our findings reveal a negative correlation between BST2+ macrophage levels and PDAC patient prognosis. Moreover, an increased ratio of exhausted CD8+ T cells is observed in tumors with up-regulated BST2+ macrophages. Mechanistically, BST2+ macrophages secrete CXCL7 through the ERK pathway and bind with CXCR2 to activate the AKT/mTOR pathway, promoting CD8+ T cell exhaustion. The combined blockade of CXCL7 and programmed death-ligand 1 successfully decelerates tumor growth. Additionally, cGAS-STING pathway activation in macrophages induces interferon (IFN)α synthesis leading to BST2 overexpression in the PDAC TME. This study provides insights into IFNα-induced BST2+ macrophages driving an immune-suppressive TME through ERK-CXCL7 signaling to regulate CD8+ T cell exhaustion in PDAC.